Exclusion of ground-nesting ants promotes biological control, but facilitates the establishment of an exotic canopy-nesting ant species - Plata, Ángel; Gómez-Martínez, María A.; Beitia, Francisco J.; Tena, Alejandro (Elsevier, 2024)
Exclusion of ground-nesting ants from tree canopies is an ant-management technique used in fruit crops. This strategy aims to disrupt the symbiotic relationship between ants and honeydew-producing herbivores, which are protected by ants, and enhance the biological control of these herbivores. Here, we evaluated this strategy to enhance the biological control of mealybugs in persimmon, but obtained an unexpected outcome. Using a randomized block design in a commercial persimmon orchard during two consecutive years, we demonstrated that physical barriers based on sticky bands excluded native ground-nesting ant species from persimmon trees and reduced the protection that these ants provided to mealybugs. The exclusion of native ground-nesting ants also increased the density and efficacy of the biological control agents of the mealybug. However, physical barriers favoured the establishment of the exotic canopy-nesting ant species Cardiocondyla obscurior. This ant species established its colonies under the sepals of persimmon fruit, and its abundance increased by more than 10 times in trees with physical barriers. Our results show that the exclusion of native ground-nesting from fruit trees can promote the control of invasive mealybugs, but may also facilitate the establishment and spread of exotic canopy-nesting ant species, hence increasing their invasive potential. Further research should evaluate alternative ant management strategies to enhance biological control of honeydew-producing herbivores without benefiting exotic canopy-nesting ant species.